2011
DOI: 10.1083/jcb.201007141
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-3–mediated signaling from multiple integrin classes is required for osteoclast-mediated bone resorption

Abstract: Loss of kindlin-3 impairs activation of β1, β2, and β3 integrin classes, resulting in osteopetrotic defects in osteoclast adhesion and spreading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
114
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 54 publications
8
114
0
Order By: Relevance
“…Kindlin-3-deficient mice die shortly after birth and suffer from severe hemorrhages, anemia, marked leukocytosis, loss of hematopoietic stem cells (HSCs) and hematopoietic progenitor cells (HPCs) from the bone marrow (BM), as well as from pronounced osteopetrosis (Fig. 3) (Moser et al, , 2009aSchmidt et al, 2011;Ruppert et al, 2015). In vitro studies of kindlin-3-deficient platelets, neutrophils and osteoclasts revealed a complete functional abrogation of integrins.…”
Section: Kindlin-3 In Hematopoietic Dysfunctions and Lad IIImentioning
confidence: 99%
See 1 more Smart Citation
“…Kindlin-3-deficient mice die shortly after birth and suffer from severe hemorrhages, anemia, marked leukocytosis, loss of hematopoietic stem cells (HSCs) and hematopoietic progenitor cells (HPCs) from the bone marrow (BM), as well as from pronounced osteopetrosis (Fig. 3) (Moser et al, , 2009aSchmidt et al, 2011;Ruppert et al, 2015). In vitro studies of kindlin-3-deficient platelets, neutrophils and osteoclasts revealed a complete functional abrogation of integrins.…”
Section: Kindlin-3 In Hematopoietic Dysfunctions and Lad IIImentioning
confidence: 99%
“…Kindlin-1 is also found outside of integrin adhesions; for example, it has been shown to translocate in an integrin-and phosphorylation-dependent manner to centrosomes, where it participates in the assembly of the mitotic spindle (see Box 2) (Patel et al, 2013). In osteoclasts, kindlin-3 is predominantly found in podosomes, which seal a membrane pocket that contains proteases and proteins that are essential for bone resorption (Schmidt et al, 2011). Kindlin-2, probably with the help of its nuclear localization signal (NLS) (Ussar et al, 2006), can localize to the nucleus of smooth muscle cells (Kato et al, 2004) and breast cancer cells (Yu et al, 2012).…”
Section: Subcellular Localisations Of Kindlinsmentioning
confidence: 99%
“…Interestingly, intracellular adapter proteins such as talin and kindlin that are involved in integrin conformational activation 59,60 are also critical to induce integrin clustering in cells plated on immobilized integrin ligands. 8,9,61 Importantly, stable integrin clustering can only be seen on immobilized ligands, again supporting the notion that talin and kindlin mediated conformational changes require the presence of ligands. This is also corroborated by studies with individual nano-disc embedded aIIbb3 integrins, the extended conformation of which increased from 10% to 20% in the presence of talin head and to at least 40% in the presence of the fibrin ligand, 62 indicating the essential role of extracellular ligands in stabilizing integrin activation and/or in assisting integrin clustering by favoring the reciprocal association of cytoplasmic adapter proteins.…”
Section: Integrin Conformational Regulation As An Example Of Allostermentioning
confidence: 60%
“…Osteoclasts generated from mice deficient in kindlin-3 lack podosomes and are unable to activate signalling downstream of b 1 , b 2 and b 3 integrins (Schmidt et al 2011), confirming the major role of integrin signalling for osteoclast adhesion and polarisation.…”
Section: Initiating Resorptionmentioning
confidence: 82%
“…Recently, it was discovered that mutations in kindlin-3, a protein that activates integrins on blood-derived lymphocytes and platelets (Moser et al 2008), result in osteopetrosis (Schmidt et al 2011). Osteoclasts generated from mice deficient in kindlin-3 lack podosomes and are unable to activate signalling downstream of b 1 , b 2 and b 3 integrins (Schmidt et al 2011), confirming the major role of integrin signalling for osteoclast adhesion and polarisation.…”
Section: Initiating Resorptionmentioning
confidence: 95%